Numerical Solution of the Variational Problem of Seismoscopy - Iwanow, Z. (Engineering Transactions, 1994)
The method for solving the variational problem of seismoscopy, submitted in the present paper, offers various possibilities for verifying the structure and the properties of a medium. This qualitatively new approximate method for solving numerically such a problem is reduced, by appropriate discretization, to an operation on graphs. An algorithm for seeking in those graphs for paths of minimum length has been worked out. It is adapted to the structure of the graphs and, therefore, is effective, if the way of discretization involves graphs with a number of vertices amounting to some millions. The method is illustrated by a simple but not trivial example, in which analytical and numerical results are compared.